Agglomeration economies in the Finnish manufacturing sector - Kirsi Mukkala (European Regional Science Association (ERSA), 2003)
Regional concentration of population and economic activity is a common phenomenon both in Finland and the other most developed countries, which refers to the existence of agglomeration economies. Two types of economies are usually recognised to be important: specialisation (Marshall externalities) and diversity (Jacobs externalities) economies. The former refer to the geographical concentration of a specific industry and the latter to the industrial diversity of the local system. This paper examines the relationship between agglomeration economies and regional productivity in the manufacturing sector in Finland. A distinction is made between the effects of urbanisation and localisation economies. The production function method is applied to the manufacturing sub-sectors in the 83 NUTS 4-level regions in 1995 and 1999. The results find in favour of regional specialisation more than diversification even if some differences can be seen between the manufacturing sub-sectors. Localisation economies seem to be stronger in the regions where the average size of firms is small, which indicates that regions with smaller firms might profit more from localisation.
Keywords: 330